Teriflunomide Treatment of Multiple Sclerosis Selectively Modulates CD8 Memory T Cells - Tilly, Gaëlle; Cadoux, Marion; Garcia, Alexandra; Morille, Jérémy; Wiertlewski, Sandrine; Pecqueur, Claire; Brouard, Sophie; Laplaud, David; Degauque, Nicolas (Frontiers in Immunology, 2021)
Background and Objectives. Inhibition of de novo pyrimidine synthesis in proliferating T and B lymphocytes by teriflunomide, a pharmacological inhibitor of dihydroorotate dehydrogenase (DHODH), has been shown to be an effective therapy to treat patients with MS in placebo-controlled phase 3 trials. Nevertheless, the underlying mechanism contributing to the efficacy of DHODH inhibition has been only partially elucidated. Here, we aimed to determine the impact of teriflunomide on the immune compartment in a longitudinal high-dimensional follow-up of patients with relapse-remitting MS (RRMS) treated with teriflunomide. Methods. High-dimensional spectral flow cytometry was used to analyze the phenotype and the function of innate and adaptive immune system of patients with RRMS before and 12 months after teriflunomide treatment. In addition, we assessed the impact of teriflunomide on the migration of memory CD8 T cells in patients with RRMS, and we defined patient immune metabolic profiles. Results. We found that 12 months of treatment with teriflunomide in patients with RRMS does not affect the B cell or CD4 T cell compartments, including regulatory TREG follicular helper TFH cell and helper TH cell subsets. In contrast, we observed a specific impact of teriflunomide on the CD8 T cell compartment, which was characterized by decreased homeostatic proliferation and reduced production of TNF and IFN. Furthermore, we showed that DHODH inhibition also had a negative impact on the migratory velocity of memory CD8 T cells in patients with RRMS. Finally, we showed that the susceptibility of memory CD8 T cells to DHODH inhibition was not related to impaired metabolism. Discussion. Overall, these findings demonstrate that the clinical efficacy of teriflunomide results partially in the specific susceptibility of memory CD8 T cells to DHODH inhibition in patients with RRMS and strengthens active roles for these T cells in the pathophysiological process of MS.